Comprehension of texts in Digital Format versus Printed Texts and Self-Regulated Learning in University Students - Paula Gabriela Flores-Carrasco; Alejandro Díaz-Mujica; Irma Elena Lagos-Herrera (Universidad Nacional, Costa Rica, 2016)
This article aims (1) to describe the levels of self-regulation and reading comprehension of scientific expository texts; (2) to establish the relationship between self-regulation and reading comprehension; and (3) to compare the performance in comprehension when the printed media (paper) or digital media (computer) is used. A quasi-experimental, quantitative, descriptive and correlative design was implemented. The sample was composed of 55 university students from four careers of Education; they were in 1st and 3rd year of study at a regional university of the Council of Rectors of Chilean Universities. Three measuring instruments were used: a questionnaire of self-regulated learning and two comprehension tests based on the understanding of Parodi's (2005) assessment model. The implementation was made in two consecutive moments; first, the self-questionnaire; then, the tests for reading comprehension in both media. With the data obtained, statistical tests of variance, one-way ANOVA, Pearson's correlation, and means comparison with Bruner and Munzel and U-Mann Whitney's tests were calculated. In conclusion, and different from the initial statement, it was obtained that university students have an adequate level of self-regulation and low reading comprehension in both data, even the scores are relatively lower in digital data. In both data the output is inverse to the complexity of the questions. Between 1st and 3rd year, there is no increase either in the self-regulation or in reading comprehension; but, exceptionally, the career of Primary General Education specialist on Language and History did. There is a strong relationship between reading comprehension in printed media and self-regulation (ARATEX). The support does not affect reading comprehension, but individual reading skills of the subjects do. A competent reader will have similar performance in both reading supports.